Autistic Community and Social Change - Τυλιγάδα, Ιωάννα (Πανεπιστήμιο Πελοποννήσου, 2023)
The online autistic community is creating safe and supportive spaces for autistic individuals to share their experiences, access valuable information, and build a sense of community, through social media. This thesis aims to explore the impact of social media creators on attitudes, perceptions, and potential social change dynamics within the online autism community. For this purpose, mixed-method research was conducted using the sequential explanatory design. The results show that the content shared by autistic social media creators has a significant impact on shifting perceptions of autism in a more inclusive and accepting direction. In addition, the results highlight the potential for broader social change driven by challenging stereotypes and advocating for inclusion. The findings suggest that social media have the potential to serve as a platform not only for information but also for personal growth and empowerment among autistic individuals, which aligns with the broader societal changes related to neurodiversity and inclusion.
Αριθμός Εισαγωγής: 013755 cd
Keywords: Διαταραχές αυτιστικού φάσματος -- Ελλάδα; Αυτισμός -- Κοινωνικές απόψεις -- Ελλάδα; Αυτιστικά άτομα -- Κοινωνικές απόψεις -- Ελλάδα; Μέσα κοινωνικής δικτύωσης -- Ελλάδα; Επικοινωνία και τεχνολογία -- Κοινωνικές απόψεις -- Ελλάδα; Autism; Traits; Social media; Disability; Neurodiversity; Identity-first language; Αυτισμός; Χαρακτηριστικά; Μέσα κοινωνικής δικτύωσης; Αναπηρία; Νευροδιαφορετικότητα